Aortic Stiffness, Increased White Matter Free Water, and Altered Microstructural Integrity: A Continuum of Injury. Issue 6 (June 2017) - Maillard, Pauline; Mitchell, Gary F.; Himali, Jayandra J.; Beiser, Alexa; Fletcher, Evan; Tsao, Connie W.; Pase, Matthew P.; Satizabal, Claudia L.; Vasan, Ramachandran S.; Seshadri, Sudha; DeCarli, Charles
Abstract : Background and Purpose—: Previous reports from the Framingham Heart Study have identified cross-sectional associations of arterial stiffness, as reflected by carotid–femoral pulse wave velocity (CFPWV) and systolic blood pressure with vascular brain injury. The purpose of this study is to examine free water (FW), fractional anisotropy (FA), and white matter hyperintensities (WMH) in relation to arterial stiffness among subjects of the Framingham Offspring and Third-Generation cohorts. Methods—: In 2422 participants aged 51.3±11.6 years, FA, FW, and WMH were related to CFPWV using voxel-based linear and generalized linear regressions, adjusting for relevant covariables. Mean FW, mean FA, and WMH burden (log transformed) were computed within white matter (WM) region and related to systolic blood pressure and CFPWV using multiple mediation analyses. Results—: CFPWV was found to be associated with higher FW, lower FA, and higher WMH incidence in WM areas covering, respectively, 356.1, 211.8, and 10.9 mL of the WM mask. Mediation analyses revealed that the effect of systolic blood pressure on FW was mediated by CFPWV (direct and indirect effects: a=0.040; P <0.001, and a′=0.020; P >0.05). Moreover, the effect of CFPWV on FA was mediated by FW (direct and indirect effects: b=−0.092; P <0.001, and b′=0.012; P >0.05), whose effect on WMH was, in turn, mediated by FA (direct and indirect effects: c=0.246; P <0.001, and c′=0.116; P >0.05). Conclusions—: From these data, we propose a biomechanical hypothesis designed for future research experiments to explain how hemodynamic alteration may lead to WM injury by impacting cerebral water content and more subtly WM integrity, to finally lead to WMH development. Abstract : Supplemental Digital Content is available in the text.